Культурне мовленнєве середовище як умова мовленнєвої культури курсантів і студентів у ЗВО - Федоренко, О. І.; Fedorenko, O. I.; Мариківська, Г. А.; Marykivska, H. A.; Федоренко Олена (The third international scientific congress of scientists of Europe as part of the III International Scientific Forum of Scientists "East - West" (Austria - Russia - Kazakhstan - Canada - Ukraine - Czech Republic), 11th January 2019, Vienna, Austria. - Vienna : Premier Publishing s.r.o., 2019. - P. 974-983, 2019)
Стаття присвячена педагогічним умовам формування мовлєннєвої культури студентів і курсантів. The article is devoted to the pedagogical conditions for the formation of the speech culture of students and cadets. Статья посвящена педагогическим условиям формирования речевой культуры студентов и курсантов.
Keywords: мовленнєва культура; speech culture; речевая культура; освітнє середовище; educational environment; образовательная среда; педагогічні умови; pedagogical conditions; педагогические условия; студенти; students; студенты; курсанти; cadets; курсанты